DUKUNGAN SOSIAL PADA MAHASISWA YANG SEDANG MENYUSUN SKRIPSI ( STUDI FENOMENOLOGIS PADA MAHASISWA FAKULTAS PSIKOLOGI UNDIP ) - Astuti, Tri Puji; Hartati, Sri (Faculty of Psychology, Diponegoro University, 2013)
As a mandatory part of an undergraduate degree in almost all universities, students are required to write their undergraduate thesis in order to receive their degree. It is not an easy job, because there are many challenges and problems while planning and writing their paper. Many students are quite frustrated and tensed as their degree depends on their final thesis submission. On the other hand, the process are not always cause the student become depresssed and fail. The condition is due to the support from the people around them. This study took a qualitative approach to explain that fenomena. The formalized question of the study is how the social support experiences impact the paper writing process. There are six (6) student of the Faculty of Psychology that participated in the study. Each respondent has a different experience with social support that they had received, and not all of them have a positive effect. Social support received by students from a variety of sources and different types of social support benefits more. Students who were interviewed stated that between parents and friends, have just as great a role but they have differences in the type of social support that fit with the students.